2000
DOI: 10.1128/jvi.74.22.10834-10837.2000
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus: Description of Persistence in Individual Pigs upon Experimental Infection

Abstract: We studied the persistence of porcine reproductive and respiratory syndrome virus (PRRSV) in individual experimentally infected pigs, during a period of up to 150 days postinfection (dpi). The results of this study suggest that the persistence of PRRSV involves continuous viral replication but that it is not a true steady-state persistent infection. The virus eventually clears the body and seems to do it in most of the animals by 150 dpi or shortly thereafter. High genetic stability was seen for several region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
132
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(146 citation statements)
references
References 16 publications
9
132
0
5
Order By: Relevance
“…Given the high specificity of the RTnPCR assay demonstrated in this experiment, i.e., 4 false positives among 780 samples from animals known to be PRRS virus negative, these results suggest the detection of inactivated virus in previously infected animals .. Overall, the results of this and previous studies are in agreement: PRRS virus infection results in persistently-infected swine (Allende et al, 2000;Christopher-Hennings et al, 1995;Christopher-Hennings et al, 2001;Wills et al, 1995;Wills et al, 1999). The current study differed from previous studies in that a higher proportion of carriers was detected than previously reported.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Given the high specificity of the RTnPCR assay demonstrated in this experiment, i.e., 4 false positives among 780 samples from animals known to be PRRS virus negative, these results suggest the detection of inactivated virus in previously infected animals .. Overall, the results of this and previous studies are in agreement: PRRS virus infection results in persistently-infected swine (Allende et al, 2000;Christopher-Hennings et al, 1995;Christopher-Hennings et al, 2001;Wills et al, 1995;Wills et al, 1999). The current study differed from previous studies in that a higher proportion of carriers was detected than previously reported.…”
Section: Discussionsupporting
confidence: 81%
“…The detection of PRRS virus in tonsil and/or oropharyngal scrapings has previously been reported (Allende et al, 2000;Benfield et al, 1997;Christopher-Hennings et al, 2001;Wills et al, 1997;Wills et al, 1999). In this study, virus was detected somewhat more frequently in oropharyngeal scraping samples than tonsil tissue samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These may nevertheless play a role in reducing the viral load (34). Of major concern to animal health is that PRRSV 1) results in persistent infections that may require 150 days to clear (46) and 2) infections increase susceptibility to secondary infection and may interfere with the success of vaccines (47)(48)(49).…”
mentioning
confidence: 99%
“…PRRSV targets primarily a subpopulation of macrophages in the lung and other tissues that have reached a specific stage of differentiation that renders them permissive to the virus (Duan et al, 1997;Gaudrealt et al, 2009). PRRSV infection is characterised by an atypical pathogenesis consisting of a prolonged acute phase lasting for 1 month or longer, with peak virus levels in the blood and lung between 7 to 14 days post infection and followed by a persistent infection in the lung and lymphoid tissues that clears for most animals within 150 days post infection (Allende et al, 2000), but can last in some (especially younger) pigs for several months or years (Lopez and Osorio, 2004;Figure 3a).…”
Section: Prrsv (Virus) Infection (See Example 1)mentioning
confidence: 99%